2021
DOI: 10.3390/ani11020255
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and Complications in a Case Series of 39 Total Laparoscopic Prophylactic Gastropexies Using a Modified Technique

Abstract: Laparoscopic-assisted, laparoscopic, and endoscopic gastropexy techniques have been proven successful in recent years. Thanks to minimal invasiveness, low morbidity, and fast recovery, total laparoscopic gastropexy techniques have been gaining popularity. The objective of this study was to describe the use of a modified minimally invasive technique to perform prophylactic gastropexy in dogs. A case series study of 39 client-owned dogs was undertaken from June 2019 to August 2020. Each dog underwent total lapar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 28 publications
1
4
2
Order By: Relevance
“…The surgical site infection rate for all abdominal surgeries in this population of dogs was 11.5%. The frequency of incision complications in this study was lower compared to a frequency of 15.5% in other studies evaluating prophylactic IG [37], LAIG [38], and TLIG [39]. This is the largest study to date reporting the outcomes and complications of prophylactic gastropexy.…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…The surgical site infection rate for all abdominal surgeries in this population of dogs was 11.5%. The frequency of incision complications in this study was lower compared to a frequency of 15.5% in other studies evaluating prophylactic IG [37], LAIG [38], and TLIG [39]. This is the largest study to date reporting the outcomes and complications of prophylactic gastropexy.…”
Section: Discussioncontrasting
confidence: 63%
“…More recently, studies by Gazzola et al and Coleman et al concluded that LAIG did not in uence GI motility based on data collected from a wireless motility device [48][49]. Three dogs (0.4%) in the present study had persistent GI signs and 11 dogs (1.4%) had transient GI signs that responded to medical therapy compared to 6.4% of dogs with GI signs reported in other studies [37][38][39]. A previous study reported the occurrence of GD in 3/27 dogs undergoing IG [37].…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…There are 3 recent studies that reported on the long-term outcomes and complications of prophylactic IG in 27 dogs in Benitez et al [ 37 ], LAIG in 44 dogs in Loy-Son et al [ 38 ], and TLIG in 39 dogs in Giaconella et al [ 39 ]. In the present study, only 3/766 dogs (0.4%) were found to have complications directly associated with the gastropexy that required surgical intervention compared to a frequency of 0–5% in the other studies evaluating prophylactic IG [ 37 ], LAIG [ 38 ], and TLIG [ 39 ]. Loy-Son et al was the only study to report the need for immediate surgical revision in 2/44 dogs (5%) due to direct gastropexy complication (gastropexy malpositioning).…”
Section: Discussionmentioning
confidence: 99%
“…Great Danes) compared with dogs that did not get a gastropexy [ 19 ]. Gastropexy is a surgical procedure involving fixation of the pyloric antrum region of the stomach to the right body wall with several techniques described [ 18 39 ]. The incidence of gastric dilatation (GD) in patients who previously underwent prophylactic incisional gastropexy (IG) was 11.1% in one report [ 37 ].…”
Section: Introductionmentioning
confidence: 99%